THE FEMINIST VOICE IN LUCILLE CLIFTON’S THE THIRTY EIGHTH YEAR, MISS ROSIE AND FINAL NOTE TO CLARK - Emilia Tetty Harjani (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study is an analysis of three poems Thirty Eighth Year, Miss Rosie and final note to clark written by Lucille Clifton, a contemporary black American poet and writer. It intends to find out what the works articulate, showing the feminist voice. The analysis was conducted sociologically based on the selection criteria that they have the same theme as the common ground, and the data were collected through library research. The results show that the speakers of the poems articulate their consciousness of self-worthvoicing basic feminist perspective against confining domestic life, white hegemonic beauty standard, and male role in black American household.